PROFIT EQUALISATION RESERVE AND INCOME SMOOTHING PRACTICES IN MALAYSIAN ISLAMIC BANKS: ROBUST STATISTICAL ANALYSIS - Noor Fadhzana Mohd Noor,; Juliza Mohamed, (Asian Academy of Management Journal, 2019)
The objective of this study is to ascertain the use of profit equalisation reserve (PER) to mitigate displaced commercial risk (DCR). This study proposes that the use of PER will be linked to smoothing practices, i.e., the earnings management (EM), capital management (CM), profit distribution management (PDM), and investment structures (IS). Using Pool and Panel OLS models, the results show that there are significant relationships between PER and CM, PDM, and long-term investment structure (LTIS). Thus, the results suggest the use of PER by banks with bigger capital to cushion for future DCR, to smooth profit pay-outs as well as its use to manage the possible DCR in LTIS. The results of this study however have failed to reject PER’s use in EM by the banks.